Information maintenance of food sources is associated with environment, spatial cognition and age in a food-caching bird. (December 2021) - Benedict, Lauren M.; Pitera, Angela M.; Branch, Carrie L.; Sonnenberg, Benjamin R.; Heinen, Virginia K.; Bridge, Eli S.; Pravosudov, Vladimir V.
Abstract : Traditionally, exploration and exploitation of resources have been viewed as mutually exclusive behaviours in which animals can either allocate time to gathering information or to using known resources. But these behaviours can also be viewed as opposite ends of a continuum, with intermediate behaviours that balance exploration and exploitation, such as information maintenance. Updating previously acquired information through information maintenance can allow animals in unpredictable environments to track changing environmental conditions. Theoretical studies predict that the degree of involvement in information maintenance should depend on environmental predictability – when the overall environment is less predictable, animals should update previously acquired information more frequently because such information is less certain and could change quickly. We tested this hypothesis by allowing wild food-caching mountain chickadees, Poecile gambeli, to visit and sample multiple feeders with temporarily stable, unlimited food for five consecutive winters. We used an index of feeder use breadth to explore how feeder visits across multiple feeders varied with environmental conditions. Each feeder visit is associated with information updating, and more information maintenance should be associated with distributing more visits across more feeders. While controlling for the total number of visits by each individual, we found that (1) chickadees redistributed feeder use among more feeders when environmental conditions were harsh and unpredictable, (2) juveniles had a higher feeder use breadth than adults, and individuals reduced their feeder use breadth as they aged, (3) better spatial learning and memory ability but not spatial cognitive flexibility was associated with smaller feeder use breadth and (4) learning associated with decreased food availability reduced subsequent feeder use breadth. Our data supported our predictions that factors affecting the predictability of resource information (environmental conditions and individual characteristics such as cognition and age) affect how individuals engage in information maintenance. Highlights: Animals should update information more frequently when the environment is unpredictable. Food-caching chickadees updated information about previously discovered food locations. Chickadees updated food information more frequently in years with harsher winters. Birds with better spatial cognition updated food information less. Older birds with more experience updated food information less.